ANALISIS KEBIJAKAN PENERIMAAN PENGUNGSI SURIAH OLEH KANADA PADA MASA PM TRUDEAU - Ressa Fatika Eldiati (Andalas Institute of International Studies, 2020)
This research will analyze Canadian policy in accepting Syrian refugees during the Trudeau period. This Canadian policy has become controversial given the issue of terrorism that is currently highlighted in the international world that these refugees could carry the threat of terrorism to other countries that result in these countries decided to reject refugees. However, despite with all of these issues Canada under the leadership of Trudeau actually decided to make a policy to accept the refugees that come to their country. This policy is completely different from the previous government which decide to reduce the entry of refugees to Canada. This research is an explanatory research through internet-based literature. Trudeau's policy in accepting Syrian refugees will be analyzed using the concept of determinants of foreign policy by William D. Coplin. There are four determinants that influence a country's foreign policy, which is, the international context, decision makers, domestic politics, and the economy and the military. This study found that of the four determinants, Canada's policy of accepting Syrian refugees during the Trudeau period was strongly influenced by public opinion in domestic political determinants, public opinion regarding the handling of refugees by Canada that had emerged since the election campaign in Canada and was Led by Trudeau to win the general election and economic conditions, Canadian needs for labour which drive the implementation of this policy. Keywords: Policy, Syria, Refugees, Canada, Trudeau